International trends in nursing care - Salazar Maya, Ángela María (Investigación y Educación en Enfermería, 2011)
Nursing care international trends, which are changing in an unexpected pace internationally, are discussed in the article. Aging, urbanization and globalization consequences accelerate the propagation of transmissible diseases worldwide, and increase the load of chronic and degenerative diseases. Health care systems contexts, every time more complex, are concerned about increases in the sanitary expenses, disparity in the health care attention and short stance hospitalization. Health care users in the future will be mostly over 65 years old, with multisystem and chronic diagnosis, with more knowledge about health, disease and the score systems of health care providers. Nursing, health care team axis will be characterized by professionals’ scarcity in a highly technological context, in which care will be based on the interpersonal multi paradigm relationship of scientific research, with a real tendency to standard care. As a discipline, nursing will keep strengthening its body knowledge. Nursing autonomy will be of great transcendence, developing own responsibilities and assuring care management.